Error‐related brain activity in young children: associations with parental anxiety and child temperamental negative emotionality. (7th January 2013) - Torpey, Dana C.; Hajcak, Greg; Kim, Jiyon; Kujawa, Autumn J.; Dyson, Margaret W.; Olino, Thomas M.; Klein, Daniel N.
<x xml:space="preserve">Abstract</x> Background: There is increasing interest in error‐related brain activity in anxiety disorders. The error‐related negativity (ERN) is a negative deflection in the event‐related potential approximately 50 ms after errors compared to correct responses. Recent studies suggest that the ERN may be a biomarker for anxiety, as it is positively associated with anxiety disorders and traits in adults and older youth. However, it is not known if the ERN in young children is related to risk for anxiety disorders. We addressed this by examining the association of six‐year olds' ERNs with two established risk factors for anxiety: parental anxiety disorder and child temperamental negative emotionality (NE). Method: The ERN was assessed using a Go/No‐Go task in a community sample of 413 six‐year olds. In a prior assessment at age 3, child temperament was evaluated using a laboratory observational measure and parental psychopathology was assessed using semi‐structured diagnostic interviews. Results: Children of mothers with anxiety disorders and children with greater temperamental NE (particularly fearfulness) exhibited significantly smaller ERNs than their peers. Paternal psychopathology, maternal mood and substance use disorders, and child positive emotionality were not associated with children's ERNs. Conclusion: Both maternal anxiety disorders and child NE (particularly fearfulness) were significantly associated with children's ERNs. However, the direction of these associations was opposite to the relations between ERNs and anxiety in older youth and adults. These results suggest that there may be a difference between risk and disorder status in the relation of error‐related brain activity to anxiety between early childhood and late childhood/ early adolescence.